Monnaie, crédit et inflation : l’analyse de Le Bourva revisitée - Jean-Luc Gaffard (Œconomia, 2020)
Monetary theory that has become dominant from the 1970 onwards is based on two main proposals: Inflation is the consequence of the excess money supply issued by a central bank obliged to follow the will of impecunious governments, and the amount of money in circulation is determined exogenously via the money multiplier. In the early 1960s, a French economist, Jacques Le Bourva, held a radically opposed approach in two articles published in Revue Économique. For him, inflation is a cumulative phenomenon that results from an excess of credit to firms, which is at the origin of imbalances on the goods markets; a budget deficit does not necessarily create inflationary pressures; credits make deposits and not the other way around; in other words, the creation of money is endogeneous. This approach is surprisingly modern when we are trying to understand the dead ends of the still dominant economic theory and policy. It helps explaining deflation as well as inflation. It is also a successful attempt to understand the articulation between monetary and fiscal policy, on the one hand, and firms’ behaviour, on the other hand.